Corporate Tax Planning and Market Value of Nigerian Listed Non-Financial Manufacturing Companies - Olawale, Bamidele Vincent; Dauda, Abdulsalam (Jurnal Akuntansi, 2025)
Purpose – This study examines the effect of corporate tax planning on the market value of Nigerian-listed non-financial manufacturing companies. Design/Methodology/Approach – The study measured market value as Tobin's Q and tax-planning intensity with the effective tax rate (ETR) and book-tax difference (BTD) over 10 non-financial firms listed on the Nigeria Exchange Group over 2014-2023. The inferential analysis used was correlation analysis and panel data regression analysis. The Hausman test was conducted, and the results indicate that the fixed effects estimation technique is more appropriate for the regression analysis. Findings – The results of this study show that there is a positive, although statistically insignificant, correlation between ETR and Tobin's Q (β = 0.28, p < 0.10), indicated that higher tax compliance is positively, yet not significantly, related to increasing investor confidence. Consistent with this, the effect of BTD on firm value is found to be positive and highly significant (β = 0.30, p < 0.01), suggesting that active tax planning or earnings management behaviors are rewarded by the market.Research limitations/Implications – The study recommended that the tax authorities should pursue more disclosure requirements to facilitate openness and that corporate managers should pursue client compliance as well as value enhancing tax strategies. This paper can be helpful to academics that investigate corporate valuation, as well as to policymakers who can ensure sustainable and transparent taxation in the developing countries. Keywords: Book-Tax Difference, Corporate Tax Planning, Effective Tax Rate, Market Value, Nigerian Manufacturing Firms